Aromatic Ketones as Mild Presodiating Reagents toward Cathodes for High‐Performance Sodium‐Ion Batteries - Zhang, Shihao; Wang, Jing; Chen, Kean; Pu, Xiangjun; Zhu, Huiying; Zhao, Yanan; Zhao, Along; Chen, Xiaoyang; Fang, Yongjin; Chen, Zhongxue; Cao, Yuliang (Angewandte Chemie International Edition, 2024)
Chemical presodiation (CP) is an effective strategy to enhance energy density of sodium ion batteries. However, the sodiation reagents reported so far are basically polycyclic aromatic hydrocarbons (PAHs) wth low reductive potential (~0.1 V vs. Na+/Na), which could easily cause over‐sodiation and structural deterioration of the presodiated cathodes. In this work, Aromatic ketones (AKs) are rationally designed as mild presodiating reagents by introducing a carbonyl group (C=O) into PAHs to balance the conjugated and inductive effect. As the representatives, two compounds 9‐Fluorenoneb (9‐FN) and Benzophenone (BP) manifest favorable equilibrium potential of 1.55 V and 1.07 V (vs. Na+/Na), respectively. Note that 9‐FN demonstrates versatile presodiating capability toward multiple Na uptake hosts (tunneled Na0.44MnO2, layered Na0.67Ni0.33Mn0.67O2, polyanionic Na4Fe2.91(PO4)2P2O7, Na3V2(PO4)3 and Na3V2(PO4)2F3), enabling greatly improved initial charging capacity of the cathode to balance the irrevisible capacity of the anode. Our results indicate that the Aromatic ketones are competitive presodiating cathodic reagents for high‐performance sodium‐ion batteries, and will inspire more studies and application attempts in the future. Aromatic ketone Na‐9‐FN‐DME is rationally designed as a mild presodiating reagent by introducing a carbonyl group into polycyclic aromatic hydrocarbons to balance the conjugated and inductive effect, thus demonstrating versatile presodiating capability toward multiple Na uptake hosts, Na0.44MnO2 as an example achieves higher charge capacity and longer life after presodiation, and manifests structural stability upon prolonged presodiation time.